IDENTIFIKASI KESALAHAN MAHASISWA MENURUT WATSON DALAM MENYELESAIKAN MASALAH FUNGSI PEMBANGKIT BERDASARKAN TIPE KEPRIBADIAN KEIRSEY - Nur Fitriyah Indraswari; Fitriana Minggani (SIGMA, 2022)
The purpose of this study is to identify the mistakes of students with artistic, idealistic, guardian, and rational personality in solving generating function problems. Qualitative is the approach in this research, while the type of research is exploratory descriptive. The instruments in this study were a mathematical ability test, the Keirsey Temprament Sorter, problem solving tasks, and interview guidelines. The validity of student error data was checked using technical triagulation. Based on the results of the study, students with artisan personalities met the criteria for missing data errors, response level conflicts, indirect manipulation, and skill hierarchical problems. Students with idealistic personality meet the criteria for missing data errors and students with guardian personalities meet the criteria for errors in skill hierarchy problems. Meanwhile, students with rational personality meet the criteria for missing data errors, missing conclusions, response level conflicts, indirect manipulation, and skill hierarchy problems. Only students with guardian personality can solve problems using the FPB concept, namely  correctly.